Where Do We Go from Here?. Issue 1 (19th December 2016) - Rutherford, Jonathan
Abstract: The left needs a fundamental rethinking of its politics for a new era. The first task is to understand the contemporary conjuncture: the dynamic combination of events and circumstances which structure a political settlement. Two such conjunctures have occurred in recent history. The first produced the postwar welfare settlement of 1945, which broke down in the economic crisis of the 1970s. The second took shape in the 1980s around the revival of liberal market economics and what became known as Thatcherism. It failed following the 2008 financial crash, and has begun to break apart with the vote to leave the EU. New political and cultural faultlines are confounding the orthodoxies of the governing class and cutting across the partisan loyalties of the main political parties. They herald the renewal of politics. But Labour is on the edge of an abyss. This article considers what the left can learn from Labour's previous periods of defeat and revisionism, and suggests where—if it survives—it should go next.